Reproductive capacity of Supputius cincticeps (Hemiptera: Pentatomidae): are females affected by continual exposure to males? - DINIZ SILVEIRA, RODRIGO; MOLINA-RUGAMA, ADRIÁN JOSÉ; ZANUNCIO, JOSÉ COLA (Revista Colombiana de Entomología, 2005)
The influence of the period of male exposure on the reproductive capacity of Supputius cincticeps (Stål) (Hemiptera: Pentatomidae) females in laboratory was studied. The experiment was conducted at a temperature of 25.0 ± 2.0oC, relative humidity 60.0 ± 10.0% and photoperiod 12 h. Females of S. cincticeps were exposed to the male for mating during their entire lifetime (T1), until laying the first egg mass (T2) and without male exposure (T3). The variables observed were number of egg masses, number and viability of the eggs and longevity of the female. The number of egg masses was similar between T1 and T2 (5.5 ± 0.88, and 4.9 ± 1.09 per female respectively), and higher than T3 (1.8 ± 0.34). The number and viability of eggs of S. cincticeps were also similar between T1 and T2, (61.0 ± 10.74 and 49.9 ± 11.97 eggs, and 62.2 ± 3.59% and 65.1 ± 4.09%, respectively). Bugs that did not mate (T3) laid fewer eggs per female (12.5 ± 2.70) and these were not viable. Longevity of females of S. cincticeps was similar among treatments with values of 28.0 ± 2.25 (T1), 24.4 ± 3.48 (T2) and 26.9 ± 2.54 (T3) days, showing that this biological characteristic is independent of mating. In terms of mass rearing, the females and males of S. cincticeps can be maintained in production for twenty to twenty five days old because during this period the bugs achieved more than 80% of total egg production.